Social Importance and Environmental Changes of Urban Springs of the City of Queimados, Brazil - Mendes, Marcos Pires (2018)
Water is indispensable to meet the basic needs of living beings, which makes scarcity somewhat alarming. This study aims to estimate the population that uses water from urban springs, understanding that this runs greater risks of water insecurity. It was made a diagnostic evaluation of the environmental characteristics of the springs and semi-structured interviews with the resident users to collect data. Each spring presented particularities, with individual detail in this study. As for the estimation of social importance, only 0.4% of the population of Queimados still uses spring water, which shows a decline in social importance. Of the remaining users, 511 are at risk of contamination.